Pemanfaatan Ikan dan Tempe untuk Kebutuhan Nutrisi Pakan Kucing Ramah Lingkungan - Moza Hanu Sabila; Roni Afriadi; Sarah Witri Tampubolon; Nazwa Nuha Nasution (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Fish waste and tempeh have significant nutritional advantages in making cat food. Some of the advantages that can be obtained from using these ingredients include the vegetable protein content in tempeh which is easier for cats to digest, making it very beneficial for cats with certain digestive sensitivities or allergies. Tempeh also contains essential amino acids that help meet the nutritional needs of cats, as well as support muscle growth and maintenance. Fish waste contains important nutrients such as 29.70% protein, 18.83% fat, 1.94% carbohydrates, 8.97% water content, and 1.07% crude fiber, which overall meet the nutritional needs of cats. In addition, the omega-3 fatty acid content in eggs is also useful for the health of the cat's skin and fur, making the food more nutritious. Tempeh is also known as first aid for cats with diarrhea, because the bacteria contained in tempeh can help neutralize harmful bacteria in the cat's intestines. By combining fish waste and tempeh in cat food, cats can get complete and balanced nutritional intake, while reducing feed production costs, making it a more environmentally friendly and economical choice.